Effects of short and long term electromagnetic fields exposure on the human hippocampus. Issue 4 (December 2017) - Deniz, Omur Gulsum; Kaplan, Suleyman; Selçuk, Mustafa Bekir; Terzi, Murat; Altun, Gamze; Yurt, Kıymet Kübra; Aslan, Kerim; Davis, Devra
Highlights: This pilot investigation of female medical students finds that electromagnetic fields exposure does not alter the volume of the human hippocampus. Widespread use of mobile phones among medical students results in a low level of concentration in the present study. Prolonged use of mobile phones can lead to a decline in the ability to suppress stimuli. Abstract: The increasing use of mobile phones may have a number of physiological and psychological effects on human health. Many animal and human studies have reported various effects on the central nervous system and cognitive performance from of exposure to electromagnetic fields (EMF) emitted by mobile phones. The aim of the present study was to evaluate the effects of mobile phones on the morphology of the human brain and on cognitive performance using stereological and spectroscopic methods and neurocognitive tests. Sixty healthy female medical school students aged 18–25 years were divided into a low exposure group (30 subjects, <30 min daily use by the head) and high exposure group (30 subjects, >90 min daily use by the head). Magnetic resonance images (MRI) of the brain analysed on OsiriX 3.2.1 workstation. Neuropsychological tests were performed for each subject. In addition, three dominant specific metabolites were analysed, choline at 3.21 ppm, creatine at 3.04 ppm and N -acetyl aspartate at 2.02 ppm. Analysis of the spectroscopic results revealed no significant difference in specific metabolites between the groups (p > 0.05). There was also no significant difference in terms of hippocampal volume between the groups (p > 0.05). In contrast, the results of the stroop and digit span (backward) neurocognitive tests of high exposure group for evaluating attention were significantly poorer from low exposure group (p < 0.05). Based on these results, we conclude that a lack of attention and concentration may occur in subjects who talk on mobile phones for longer times, compared to those who use phones relatively less.